Once upon a timeless tale collection [compact disc, unabridged] - Andersen, H. C. (Hans Christian), 1805-1875 (Bolinda Audio, 2015)
Once Upon a Timeless Tale Collection is a contemporary retelling of the most well-known and best-loved fairy tales of all time. Traditional stories from Hans Christian Andersen and Charles Perrault are brought alive for a fresh generation of listeners, giving these timeless classics a new lease of life.